On the Method of Masking in the Multiple Signature Protocol Based on Isogenies of Elliptic Curves - Aleksandrova, E. B.; Kostin, S. O. (Automatic control and computer sciences, 2024)
Among the post-quantum algorithms selected by the National Institute of Standards and Technology (NIST) for standardization, the main mathematical apparatus is the mechanism of algebraic lattices, while the apparatus of hash functions is an alternative. Unlike isogenies of elliptic curves, these mechanisms use larger sizes of both public keys and signatures. Using the example of a multiple signature protocol based on isogenies of elliptic curves, we will show how, using the masking method, we can protect against the main attack on the given device, while obtaining a smaller signature size.